African Agricultural Research Capabilities (The National Academies Press, 1974)

Insect-Plant Interactions (The National Academies Press, 1969)

Cotton Boll Weevil: An Evaluation of USDA Programs : a Report - National Research Council (The National Academies Press, 1981)

Control of Plant-Parasitic Nematodes - National Research Council (The National Academies Press, 1968)

Insect-Pest Management and Control - National Research Council (The National Academies Press, 1969)

Agricultural Development and Environmental Research: American and Czechoslovak Perspectives: Proceedings of a Bilateral Workshop (The National Academies Press, 1987)

Workshop on Biotechnology in Agriculture: Summary Report, Jakarta, Indonesia, March 13-14, 1986 - National Research Council (The National Academies Press, 1986)

Races of Maize in Brazil and Other Eastern South American Countries (The National Academies Press, 1958)

Ecologically Based Pest Management: New Solutions for a New Century - National Research Council (The National Academies Press, 1996)
Widespread use of broad-spectrum chemical pesticides has revolutionized pest management. But there is growing concern about environmental contamination and human health risks2014and continuing frustration over the ability of pests to develop resistance to pesticides. In Ecologically Based Pest Management, an expert committee advocates the sweeping adoption of ecologically based pest management (EBPM) that promotes both agricultural productivity and a balanced ecosystem. This volume offers a vision and strategies for creating a solid, comprehensive knowledge base to support a pest management system that incorporates ecosystem processes supplemented by a continuum of inputs2014biological organisms, products, cultivars, and cultural controls. The result will be safe, profitable, and durable pest management strategies. The book evaluates the feasibility of EBPM and examines how best to move beyond optimal examples into the mainstream of agriculture. The committee stresses the need for information, identifies research priorities in the biological as well as socioeconomic realm, and suggests institutional structures for a multidisciplinary research effort. Ecologically Based Pest Management addresses risk assessment, risk management, and public oversight of EBPM. The volume also overviews the history of pest management2014from the use of sulfur compounds in 1000 B.C. to the emergence of transgenic technology. Ecologically Based Pest Management will be vitally important to the agrichemical industry; policymakers, regulators, and scientists in agriculture and forestry; biologists, researchers, and environmental advocates; and interested growers.

The Impact of Genetically Engineered Crops on Farm Sustainability in the United States - National Research Council (The National Academies Press, 2010)
Since genetically engineered (GE) crops were introduced in 1996, their use in the United States has grown rapidly, accounting for 80-90 percent of soybean, corn, and cotton acreage in 2009. To date, crops with traits that provide resistance to some herbicides and to specific insect pests have benefited adopting farmers by reducing crop losses to insect damage, by increasing flexibility in time management, and by facilitating the use of more environmentally friendly pesticides and tillage practices. However, excessive reliance on a single technology combined with a lack of diverse farming practices could undermine the economic and environmental gains from these GE crops. Other challenges could hinder the application of the technology to a broader spectrum of crops and uses. Several reports from the National Research Council have addressed the effects of GE crops on the environment and on human health. However, The Impact of Genetically Engineered Crops on Farm Sustainability in the United States is the first comprehensive assessment of the environmental, economic, and social impacts of the GE-crop revolution on U.S. farms. It addresses how GE crops have affected U.S. farmers, both adopters and nonadopters of the technology, their incomes, agronomic practices, production decisions, environmental resources, and personal well-being. The book offers several new findings and four recommendations that could be useful to farmers, industry, science organizations, policy makers, and others in government agencies.

Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia - National Research Council (The National Academies Press, 2009)
Increased agricultural productivity is a major stepping stone on the path out of poverty in sub-Saharan Africa and South Asia, but farmers there face tremendous challenges improving production. Poor soil, inefficient water use, and a lack of access to plant breeding resources, nutritious animal feed, high quality seed, and fuel and electricity-combined with some of the most extreme environmental conditions on Earth-have made yields in crop and animal production far lower in these regions than world averages. Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia identifies sixty emerging technologies with the potential to significantly improve agricultural productivity in sub-Saharan Africa and South Asia. Eighteen technologies are recommended for immediate development or further exploration. Scientists from all backgrounds have an opportunity to become involved in bringing these and other technologies to fruition. The opportunities suggested in this book offer new approaches that can synergize with each other and with many other activities to transform agriculture in sub-Saharan Africa and South Asia.

A Review of the Citrus Greening Research and Development Efforts Supported by the Citrus Research and Development Foundation: Fighting a Ravaging Disease - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Huanglongbing (HLB) or citrus greening, first observed more than a hundred years ago in Asia, is the most serious disease threat to the citrus-growing industry worldwide due to its complexity, destructiveness, and incalcitrance to management. First detected in Florida in 2005, HLB is now widespread in the state and threatens the survival of the Florida citrus industry despite substantial allocation of research funds by Florida citrus growers and federal and state agencies. As the HLB epidemic raged in 2008, Florida citrus growers began allocating funds for HLB research in hopes of finding short-, medium-, and long-term solutions. This effort created the Citrus Research and Development Foundation (CRDF), an organization with oversight responsibility for HLB research and development efforts in Florida. This report provides an independent review of the portfolio of research projects that have been or continue to be supported by the CRDF. It seeks to identify ways to retool HLB research2014which, despite significantly increasing understanding of the factors involved in HLB, has produced no major breakthroughs in controlling the disease2014and accelerate the development of durable tools and strategies that could help abate the damage caused by HLB and prevent the possible collapse of the Florida citrus industry.

The Future Role of Pesticides in US Agriculture - National Research Council
Although chemical pesticides safeguard crops and improve farm productivity, they are increasingly feared for their potentially dangerous residues and their effects on ecosystems. The Future Role of Pesticides explores the role of chemical pesticides in the decade ahead and identifies the most promising opportunities for increasing the benefits and reducing the risks of pesticide use. The committee recommends R&D, program, and policy initiatives for federal agriculture authorities and other stakeholders in the public and private sectors. This book presents clear overviews of key factors in chemical pesticide use, including: Advances in genetic engineering not only of pest-resistant crops but also of pests themselves. Problems in pesticide use2014concerns about the health of agricultural workers, the ability of pests to develop resistance, issues of public perception, and more. Impending shifts in agriculture2014globalization of the economy, biological \

Strategic Planning for the Florida Citrus Industry: Addressing Citrus Greening Disease - National Research Council (The National Academies Press, 2010)
Citrus greening, a disease that reduces yield, compromises the flavor, color, and size of citrus fruit and eventually kills the citrus tree, is now present in all 34 Floridian citrus-producing counties. Caused by an insect-spread bacterial infection, the disease reduced citrus production in 2008 by several percent and continues to spread, threatening the existence of Florida's 9.3 billion citrus industry. A successful citrus greening response will focus on earlier detection of diseased trees, so that these sources of new infections can be removed more quickly, and on new methods to control the insects that carry the bacteria. In the longerterm, technologies such as genomics could be used to develop new citrus strains that are resistant to both the bacteria and the insect.

Feasibility of Using Mycoherbicides for Controlling Illicit Drug Crops - National Research Council (The National Academies Press, 2011)
The control of illicit-drug trafficking and drug use is a difficult and complex process that involves a variety of prevention, control, treatment, and law enforcement strategies. Eradication strategies for controlling illicit-drug crops are used to target the beginning of the drug-supply chain by preventing or reducing crop yields. Mycoherbicides have been proposed as an eradication tool to supplement the current methods of herbicide spraying, mechanical removal, and manual destruction of illicit-drug crops. Some people regard them as preferable to chemical herbicides for controlling illicit-drug crops because of their purported specificity to only one plant species or a few closely related species. As living microorganisms, they have the potential to provide long-term control if they can persist in the environment and affect later plantings. Research on mycoherbicides against illicit-drug crops has focused on three pathogens: Fusarium oxysporum f.sp. cannabis for cannabis (Cannabis sativa), F. oxysporum f.sp. erythroxyli for coca (Erythroxylum coca and E. novogranatense), and Crivellia papaveracea or Brachycladium papaveris (formerly known as Pleospora papaveracea and Dendryphion penicillatum, respectively) for opium poppy (Papaver somniferum). Feasibility of Using Mycoherbicides for Controlling Illicit Drug Crops addresses issues about the potential use of the proposed mycoherbicides: their effectiveness in eradicating their target plants; the feasibility of their large-scale industrial manufacture and delivery; their potential spread and persistence in the environment; their pathogenicity and toxicity to nontarget organisms, including other plants, fungi, animals, and humans; their potential for mutation and resulting effects on target plants and nontarget organisms; and research and development needs. On the basis of its review, the report concludes that the available data are insufficient to determine the effectiveness of the specific fungi proposed as mycoherbicides to combat illicit-drug crops or to determine their potential effects on nontarget plants, microorganisms, animals, humans, or the environment. However, the committee offers an assessment of what can and cannot be determined at the present time regarding each of the issues raised in the statement of task.

Managing Global Genetic Resources: Agricultural Crop Issues and Policies - National Research Council (The National Academies Press, 1993)
This anchor volume to the series Managing Global Genetic Resources examines the structure that underlies efforts to preserve genetic material, including the worldwide network of genetic collections; the role of biotechnology; and a host of issues that surround management and use. Among the topics explored are in situ versus ex situ conservation, management of very large collections of genetic material, problems of quarantine, the controversy over ownership or copyright of genetic material, and more.

Publicly Funded Agricultural Research and the Changing Structure of U.S. Agriculture - National Research Council (The National Academies Press, 2002)
The U.S. Department of Agriculture (USDA) requested that the Board on Agriculture and Natural Resources of the National Research Council (NRC) convene a panel of experts to examine whether publicly funded agricultural research has influenced the structure of U.S. agriculture and, if so, how. The Committee to Review the Role of Publicly Funded Agricultural Research on the Structure of U.S. Agriculture was asked to assess the role of public-sector agricultural research on changes in the size and numbers of farms, with particular emphasis on the evolution of very-large-scale operations.

Precision Agriculture in the 21st Century: Geospatial and Information Technologies in Crop Management - National Research Council (The National Academies Press, 1997)
Sensors, satellite photography, and multispectral imaging are associated with futuristic space and communications science. Increasingly, however, they are considered part of the future of agriculture. The use of advanced technologies for crop production is known as precision agriculture, and its rapid emergence means the potential for revolutionary change throughout the agricultural sector. Precision Agriculture in the 21st Century provides an overview of the specific technologies and practices under the umbrella of precision agriculture, exploring the full implications of their adoption by farmers and agricultural managers. The volume discusses how precision agriculture could dramatically affect decisionmaking in irrigation, crop selection, pest management, environmental issues, and pricing and market conditions. It also examines the geographical dimensions2014farm, regional, national2014of precision agriculture and looks at how quickly and how widely the agricultural community can be expected to adopt the new information technologies. Precision Agriculture in the 21st Century highlights both the uncertainties and the exciting possibilities of this emerging approach to farming. This book will be important to anyone concerned about the future of agriculture: policymakers, regulators, scientists, farmers, educators, students, and suppliers to the agricultural industry.

Frontiers in Agricultural Research: Food, Health, Environment, and Communities - National Research Council (The National Academies Press, 2003)
This report is a congressionally mandated review of the US Department of Agriculture2019s Research, Education, and Economics (REE) mission area, the main engine of publicly funded agricultural research in the United States. A changing social and scientific context of agriculture requires a new vision of agricultural research – one that will support agriculture as a positive economic, social, and environmental force. REE is uniquely positioned to advance new research frontiers in environment, public health, and rural communities. The report recommends that REE be more anticipatory and strategic in its use of limited resources and guide and champion new directions in research.

Pesticide Resistance: Strategies and Tactics for Management - National Research Council (The National Academies Press, 1986)
Based on a symposium sponsored by the Board on Agriculture, this comprehensive book explores the problem of pesticide resistance; suggests new approaches to monitor, control, or prevent resistance; and identifies the changes in public policy necessary to protect crops and human health from the ravages of pests. The volume synthesizes the most recent information from a wide range of disciplines, including entomology, genetics, plant pathology, biochemistry, economics, and public policy. It also suggests research avenues that would indicate how to counter future problems. A glossary provides the reader with additional guidance.